ANALISIS KESULITAN SISWA TERHADAP PEMAHAMAN KONSEP SISTEM PERSAMAAN LINIER DUA VARIABEL (SPLDV) - Amir, Almira (IAIN PADANGSIDIMPUAN, 2017)
The background of the problem in this research is the difficulties of students in studying and understanding the concept of two-variable linear equation system (SPLDV) in class VII SMP Negeri 7 Padangsidimpuan. From the above background, this study aims to determine the level of difficulty of students to understanding the concept of two-variable linear equation system, to know the factors that cause student learning difficulties and how the teacharâ€™s efforts overcome the studentâ€™s learning difficulties.This research is a qualitative research. The sources of this research are students and teachers of VII mathematics class at SMP Negeri 7 Padangsidimpuan. Then the instrument in thisÂ research is observation, interview and test.Base on the result of the study of mathematics learning difficulties to the understanding of the concept of two-variable linear equation system (SPLDV) is that students do not understand the concept of algebra calculation, in other words the students still do not understand the counting operation on the algebra. Carelessness done by students in answering the matter of system linear equations of two variables, it is because students rush or see other students wrong. Error principle of operation count on system of linear equation of two variable often happened done student especially student not pay attention to sign of negative and positive. Factors causing student learning difficulties are caused by two external and internal factors of students. The dominant factor that cause the difficulties of learning the students is the motivation of students who are less in learning mathematics. While the efforts made by mathematics teachers in overcoming the difficulties of students is to focus more on the understanding of the concepts in learning mathematics, especially on SPLDV, member motivation to students and give special attention to students who have difficulty in learning the system of two linear equations